From surgical anatomy to microscopy: visualizing choroid plexus and its role in headache research - Andrade, Juliana Ramos de (2024)
The choroid plexus (ChP) is pivotal in cerebrospinal fluid (CSF) production, intracranial pressure regulation, and brain homeostasis, intricately linked to headache pathophysiology. This study integrates macroscopic, microsurgical, and microstructural analyses to explore the anatomy and function of the ChP, highlighting its structural and functional significance.MethodsMacroscopic and microsurgical dissections were performed on cadaveric specimens, with arteries and veins injected with colored silicone to enhance visualization. Microstructural analysis was conducted using scanning electron microscopy to reveal detailed surface morphology.ResultsThe ChP in the lateral ventricles exhibits a characteristic C-shaped configuration, attached to the taenia along the choroidal fissure, a critical surgical landmark. Microsurgical views emphasize the ChP at the interventricular foramen, a key region frequently encountered during neurosurgical procedures. The ChP’s luminal surface displays intricate architecture, including villi, microvilli, cilia, and interdigitations, reflecting its active role in CSF dynamics.ConclusionsThese findings underscore the ChP’s specialized surface features and cellular organization, which are fundamental for maintaining CSF homeostasis and regulating intracranial pressure. Disruptions in ChP morphology or function could contribute to headache development, particularly in conditions associated with CSF flow and pressure dysregulation. By bridging macroscopic neuroanatomy, microsurgical techniques, and ultrastructural insights, this study lays the groundwork for future research into the ChP’s involvement in headache pathophysiology and its potential as a therapeutic target. Exploring this vital yet underexplored structure in neuroscience offers promising avenues for advancing our understanding of neurological disorders.